2014
DOI: 10.2478/vzoo-2014-0047
|View full text |Cite
|
Sign up to set email alerts
|

First Records and Comparative Notes of Twelve Aphidiid Species (Hymenoptera, Aphidiidae) from the Fauna of Ukraine

Abstract: First Records and Comparative Notes of Twelve Aphidiid Species (Hymenoptera, Aphidiidae) from the Fauna of Ukraine. Kaliuzhna, M. O. - Twelve aphidiid species are recorded from the fauna of Ukraine for the first time. Localities, hosts, distribution, and comparative notes on morphology of these species are given.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 2 publications
1
8
0
Order By: Relevance
“…Few natural enemies have been reported on Eulachnus aphids (Kaliuzhna, 2014; Kavallieratos et al ., 2016). In our study, four ladybird species (Coccinellidae) were collected with peak populations synchronized with the peak of the aphid population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Few natural enemies have been reported on Eulachnus aphids (Kaliuzhna, 2014; Kavallieratos et al ., 2016). In our study, four ladybird species (Coccinellidae) were collected with peak populations synchronized with the peak of the aphid population.…”
Section: Discussionmentioning
confidence: 99%
“…A survey conducted on conifer aphids and their natural enemies in Spain detected no natural enemy feeding on this species (Nunez‐Perez & Tizado, 1996). Three other Eulachnus species, E. agilis (Kaltenbach), E. mediterraneus Binazzi and E. tuberculostemmatus , have been reported as the main hosts of Diaeretus leucopterus (Haliday) (Hymenoptera: Braconidae) and Praon bicolor Mackauer (Hymenoptera: Braconidae) on Pinus (Kaliuzhna, 2014; Kavallieratos et al ., 2016).…”
Section: Introductionmentioning
confidence: 99%
“…). In Europe, T. deltiger has been recorded to parasitize the cereal aphid Metopolophium dirhodum (Walker) (Mackauer & Starý ; Powell ; Pankanin‐Franczyk & Sobota ; Starý ) and aphids occurring in forest habitats (Kaliuzhna ).…”
Section: Discussionmentioning
confidence: 99%
“…Material: Kyiv Region: (Kaliuzhna, 2014); 1 , Kyiv city, on Salix sp., 17.06.2015 (M. Kaliuzhna).…”
Section: Adialytus Salicaphis (Fitch 1855)mentioning
confidence: 99%
“…Molecular analysis on the basis of COI gene barcoding showed that A. ambiguus and A. salicaphis are closely related species, and COI gene could not diff erentiate them well enough (Stanković et al, 2015). Despite the morphological uniformity of these species, several diagnostic characters are visible, including a diff erence in wing width of A. ambiguus and A. salicaphis (Kaliuzhna, 2014); the latter character was confi rmed by geometric morphometry method (Stanković et al, 2015).…”
Section: Introductionmentioning
confidence: 99%